The Evolution of Employment Law and Its Impact on Workplace Dynamics - Fauzi, Fahrul Ahmad; Ibrahim, Muhdi B. Hi; Irawan, Andri; Akbar, Muhammad Aldrin; Yendra, Yendra (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study investigates the evolution of employment law and its consequential impact on contemporary workplace dynamics. The research aims to elucidate the developmental trajectory of employment law and how these legal frameworks influence organizational behavior and labor market outcomes. Research Design and Methodology: A comprehensive review of pertinent literature was conducted, employing a qualitative, descriptive research methodology. This approach involved systematic examination and synthesis of existing studies, providing a nuanced understanding of the historical antecedents and contemporary phenomena influencing employment law. Findings and Discussion: The findings reveal that employment law has significantly evolved from its nascent stages during the Industrial Revolution to the complex legal frameworks of today. Key developments include establishing minimum wage laws, anti-discrimination statutes, and regulations addressing non-standard employment forms. The study highlights the impact of these legal changes on organizational practices, employee well-being, and broader economic dynamics. Technological advancements and globalization are critical drivers of recent legal adaptations, raising new challenges and opportunities within the gig economy and digital workspaces. Implications: The evolution of employment law underscores the importance of robust legal protections for promoting fair and equitable workplaces. Policymakers and organizational leaders are encouraged to continuously adapt legal frameworks to address emerging challenges, ensuring the protection of workers' rights, and fostering inclusive and dynamic work environments. Further interdisciplinary research is essential to inform effective policy interventions and enhance the adaptability of employment law in the face of ongoing socio-economic transformations.